RiskEstim: A Software Package to Quantify COVID-19 Importation Risk - Xu, Mingda; Du, Zhanwei; Shan, Songwei; Xu, Xiaoke; Bai, Yuan; Wu, Peng; Lau, Eric H. Y.; Cowling, Benjamin J. (Frontiers in Physics, 2022)
We present an R package developed to quantify coronavirus disease 2019 (COVID-19) importation risk. Quantifying and visualizing the importation risk of COVID-19 from inbound travelers is urgent and imperative to trigger public health responses, especially in the early stages of the COVID-19 pandemic and emergence of new SARS-CoV-2 variants. We provide a general modeling framework to estimate COVID-19 importation risk using estimated pre-symptomatic prevalence of infection and air traffic data from the multi-origin places. We use Hong Kong as a case study to illustrate how our modeling framework can estimate the COVID-19 importation risk into Hong Kong from cities in Mainland China in real time. This R package can be used as a complementary component of the pandemic surveillance system to monitor spread in the next pandemic.